2023
DOI: 10.7759/cureus.36684
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship Between Smoking and Insulin Resistance: A Case-Control Study

Abstract: Introduction: In recent years, there has been a surge in research focusing on the link between smoking and insulin resistance in the context of obesity and diabetes. In this study, our objective was to investigate the relationship between smoking and insulin resistance. Materials and Methods: This is a case-control study. The case and control groups were formed using the hospital patient information database and clinically randomized using data obtained, including age, gender, height, and weight. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The relationship between smoking and insulin resistance is frequently reported but the underlying mechanisms are not fully understood. However, studies show that nicotine stimulates catecholamine-mediated glucagon release from the adrenal medulla, which further increases gluconeogenesis thus causing hyperglycemia [ 187 ]. In another cell culture study, it was recapitulated that nicotine stimulated p44/p42 MAPK and mTOR signaling pathway thereby causing insulin resistance and glucose intolerance.…”
Section: Factors Leading To Development Of T2dmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between smoking and insulin resistance is frequently reported but the underlying mechanisms are not fully understood. However, studies show that nicotine stimulates catecholamine-mediated glucagon release from the adrenal medulla, which further increases gluconeogenesis thus causing hyperglycemia [ 187 ]. In another cell culture study, it was recapitulated that nicotine stimulated p44/p42 MAPK and mTOR signaling pathway thereby causing insulin resistance and glucose intolerance.…”
Section: Factors Leading To Development Of T2dmentioning
confidence: 99%
“…Additionally, it was found that smokers had greater IRS-1 ser636 phosphorylation as compared to non-smokers which may be implicated in the insulin resistance of smoking [ 188 ]. On the contrary, some studies have found no notable association between smoking and insulin resistance in healthy individuals suggesting that smoking may result in transitory stimulation of these pathways or are both the outcomes of underlying pathophysiological mechanisms that are not entirely elucidated thus challenging the prevailing notion of smoking as a key risk factor for insulin resistance [ 187 , 188 ].…”
Section: Factors Leading To Development Of T2dmentioning
confidence: 99%
“…HbA1c levels are normal if <5.7%, prediabetes 5.7 to 6.4%, and diabetes ≥6.5% 10 . Nicotine, the main compound in cigarettes, was considered most responsible for increasing blood sugar levels due to insulin resistance 11 . Nicotine is primarily metabolized by the CYP2A6 enzyme to cotinine and excreted in the urine 12 .…”
Section: Introductionmentioning
confidence: 99%